2017
DOI: 10.1016/j.yjmcc.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin signaling in the heart: The importance of time and place

Abstract: The calcium-activated protein phosphatase, calcineurin, lies at the intersection of protein phosphorylation and calcium signaling cascades, where it provides an essential nodal point for coordination between these two fundamental modes of intracellular communication. In excitatory cells, such as neurons and cardiomyocytes, that experience rapid and frequent changes in cytoplasmic calcium, calcineurin protein levels are exceptionally high, suggesting that these cells require high levels of calcineurin activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 289 publications
(302 reference statements)
3
80
0
Order By: Relevance
“…A cardiac-specific Cn knockout mouse was recently generated [7,8], but in this model, cardiac Cn deletion is not inducible and begins at the perinatal stage, resulting in impaired contractility and cardiac growth, and death between 4 and 6 months after birth [7,8]. The differences between these results and ours suggest that Cn plays different roles in cardiac homeostasis during postnatal development and adulthood and are consistent with data showing that Cn signaling differs between neonatal and adult cardiomyocytes [43].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A cardiac-specific Cn knockout mouse was recently generated [7,8], but in this model, cardiac Cn deletion is not inducible and begins at the perinatal stage, resulting in impaired contractility and cardiac growth, and death between 4 and 6 months after birth [7,8]. The differences between these results and ours suggest that Cn plays different roles in cardiac homeostasis during postnatal development and adulthood and are consistent with data showing that Cn signaling differs between neonatal and adult cardiomyocytes [43].…”
Section: Discussionsupporting
confidence: 87%
“…An alternative hypothesis consistent with our results is that, in addition to its well-known phosphatase action, cardiac Cn is essential for the assembly of molecular signaling complexes in specific cardiomyocyte subdomains that could be implicated in AngII-induced fibrosis. Supporting this idea, anchoring of Cn to the sarcomere Zdisk is critical for the integration of cardiomyocyte stress signals [43]. Other possible explanations for divergent effects on AngII-induced cardiac fibrosis in two approaches to Cn inhibition may lie in the intricate intercellular cross talk between fibroblasts and cardiomyocytes that have been described during AngII-cardiac remodeling [56].…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by processes in the excitable tissues, heart and brain, where roles of Ca 2+ and CN signaling are well documented. CN signaling dramatically impacts heart development and function via regulation of NFAT, and is known to signal from cardiac Z discs, components of which are enriched in the CNome ( Figure 7C) (Parra and Rothermel, 2017) (Chang et al, 2004;Wilkins and Molkentin, 2004). Moreover, proteins in the CNome align with the pleiotropic consequences of CN deletion in mouse cardiomyocytes (Maillet et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment of AS, the activities significantly recovered. CaN could be activated by calcium-calmodulin, and it was essential for a number of signal transduction pathways [22]. The results in Fig.…”
Section: Effect Of As On Haemodynamicsmentioning
confidence: 92%
“…CaN was ubiquitous in cells and was activated by the binding of calcium. Recent studies have shown that CaN played an important role in the apoptosis induced by MIRI [22]. CaN was also reported to be a multifunctional signal enzyme downstream of calcium signaling, and was involved in signal transmission of hypertrophy, proliferation and apoptosis [41].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%